Critical Studies of Technology, Psychology, and Education on Online Games - Dwi Sulisworo; Ratna Yunita Setiyani; Khairul Shafee Kalid; Vera Yuli Erviana (The Indonesian Institute of Science and Technology Research, 2022)
nline games are developing rapidly and have an impact on children's behaviour. This study aims to explain the phenomenon of online game addiction from the perspective of psychology, technology, and education. The method is narratively qualitative—data obtained from online focus group discussions. The results of this study explain that online games today tend towards addictive behaviour. This situation is supported by the use of current technology in programming that allows the provision of varied features to increase the game's attractiveness. This addictive behaviour affects other behaviours that can affect the development of attitudes. This behaviour change affects learning performance. The teacher should adjust learning strategies in the digital era to adapt to children's new behaviours today related to online games.